Impact of steric constraints on the product distribution of phosphate-branched oligonucleotide models of the large ribozymes - Lonnberg T; Kero KM (ROYAL SOC CHEMISTRY, 2022)
To assess the extent to which steric constraints may influence the product distribution of the reactions of the large ribozymes, phosphate-branched oligonucleotides of varying length and sequence have been synthesized and their alkaline hydrolysis studied over a wide temperature range. At low temperatures, the branching trinucleoside-3 ',3 ',5 '-monophosphate moiety is hydrolyzed almost exclusively by P-O3 ' fission. At higher temperatures, P-O5 ' fission competes, accounting at most for 22% of the overall reaction. The results suggest that steric constraints imposed by the secondary structure of the reaction site may significantly contribute to the observed regioselectivity of the transesterification reactions catalyzed by the large ribozymes.